Influence of soil water potential in the action of herbicides on goosegrass (Eleusine indica (L) Gaertn) - Maria Renata Rocha Pereira; Guilherme Sasso Ferreira de Souza; José Iran Cardoso da Silva; Ana Cláudia Macedo; Dagoberto Martins (Bioscience Journal, 2014)
Currently, the use of herbicides is essential in a practical and common in agricultural areas, but efficiency of these herbicides can be compromised when applied on plants that thrive in water deficit conditions, due to low uptake and translocation of the product. Therefore, the aim of this study was to compare the efficiency of control ACCase inhibiting herbicides applied post-emergence in plants of Eleusine indica under different soil water contents. The experiment was conducted in a greenhouse and the experimental design was completely randomized design with four replications, consisting of a 9x4 factorial, with the combination of three soil water potentials (-0.03, -0.07 and -1.5 MPa) three herbicides (fluazifop-p -butyl, haloxyfop-methyl and sethoxydim + oil) and four doses (0, 25, 50, and 100 % of the recommended dose). Herbicide application was made in plants in vegetative stage 2-3 tillers. The soil water potential was initiated in the development stage of two leaves, and the water was supplemented until the soil reaches the potential of -0.01 MPa, when it came to minimum pre-determined for each water management. The physiological parameters evaluated were: photosynthetic rate, stomatal conductance, transpiration leaf temperature and plant dry mass. The visual assessments of phytotoxicity were performed at 7 and 14 days after application. The herbicides behaved in different ways according to the used water management. In severe water stress conditions (soil moisture at 8%) only fluazifop-p-butyl herbicide achieved satisfactory control (>90%) in E. indica plants.